Field examination of the hydrological behaviour of a typical vertisol in a cropped area - Cavazza L.; Guarnieri A.; Patruno A.; Cirillo E.; Lorenzini G.; Piana S. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
The site was selected in a cropped area on a typical vertisol, fairly uniform in depth, down to about 2.5 m. It was difficult to install anchored rods and piezometers at different depths (0.2-0.3-0.4-0.5-1-1.5-2 m and 2.5 m for piezometers). Soil moisture was monitored for a certain time by drilling the ground and soil samples were dried in an oven. Cases studied were: (A) a period of dry months with severe drought (10.4 mm in 132 days);(B) a second period with exceptionally uniform precipitation (about 3.5 mm/day during 2 months). These seasonal conditions permitted the following observations: for (A) the swelling of the soil in the lower extreme cannot be strictly compared to Philip's (1969) concept of a free expansion of the water ponding on soil due to the overburdening of different conditions; for (B) the expected tendency to begin a stationary water flux depends strongly on the water regime in the previous period. In a dry period, the water accumulates in the deepest piezometers, being fed by water from the upper source at a progressively increasing rate of water rise. The regime of stable water flux is therefore delayed. The hydraulic conductivity changes in different soil layers according to the water content.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)